Estudio de la eficiencia energética en la generación fotovoltaica, a partir de diferentes tecnologías y sus componentes. - Constante Acosta, Ángel Antonio (2023)
The purpose of the following work is to study the energy efficiency of the different components that contain photovoltaic generation, such as solar panels, batteries, the inverter and the energy converter, since as we know electricity is one of the more versatile energies that adapt to each of our needs. Therefore, to be very clear about the operation of photovoltaic generation, a brief review of the state of the art of energy and radiation alone is carried out, which is one of the fundamental factors and to observe the state of the power quality of the electrical system. to later be able to see the impact generated by the quality of energy caused by solar panels.